KEMAMPUAN MENGANALISIS STRUKTUR DAN KAIDAH KEBAHASAAN TEKS EKSPOSISI OLEH SISWA KELAS VII SMP PAB 5 PATUMBAK TAHUN PEMBELAJARAN 2022-2023 - Amalia Adistri; Pita` Patria (Jurnal Inovasi Penelitian, 2023)
The lack of students' ability in learning Indonesian, especially in the ability to write expository texts, is influenced by their lack of interest in learning Indonesian. This study aims to determine the ability of students to analyze the structure and linguistic rules of exposition texts in class VII SMP PAB 5 Patumbak in the academic year 2022-2023. The subjects in this study were class VII students of SMP PAB 5 Patumbak in the academic year 2022-2023, totaling 32 students. The method used in this research is descriptive quantitative method. Based on the calculations that have been made for the assessment of the structure of the exposition text in the aspect of thesis analysis, arguments and reaffirmation, it is stated that 14 students or as many as 44% get a score above the average, which is 70.4. While the rest, namely 17 students or as much as 54% did not manage to get the average value of the class. Based on the calculations that have been carried out for the assessment of the results of students' abilities in analyzing the linguistic rules of the exposition text on the technical aspects, causal conjunctions, mental verbs and persuasive statements, it was stated that 14 students or 44% got scores above the average, namely 69, 4. While the rest, namely 17 students or as much as 54% did not manage to get the average value of the class. From the results of this study it was found that based on the calculations that have been made for the recapitulation of the assessment on the results of students' abilities in analyzing the structure and linguistic rules of the exposition text, 18 students or 56% got an above average score, which is 70.0. While the rest, namely 14 students or as much as 44% did not manage to get the average grade VII-2 SMP PAB 5 Patumbak.